Computational analysis of strain-induced effects on the dynamic properties of C60 in fullerite - Lun-Fu, Aleksandr V.; Bubenchikov, Alexey M.; Bubenchikov, Mikhail A.; Ovchinnikov, Vyacheslav A. (Crystals)
A hybrid discrete-continuous physical and mathematical model is used to study what deformation characteristics cause the rolling effect of C-60 fullerene in a fullerite crystal. The interaction of fullerene atoms with surrounding molecules is described using a centrally symmetric interaction potential, in which the surrounding molecules are considered as a spherical surface of uniformly distributed carbon atoms. The rotational motion of fullerene is described by the Euler dynamic equations. The results of a numerical study of the influence of the rate, magnitude, and direction of strain on the dynamic characteristics of the rotational and translational motion of C-60 fullerene in a crystalline fragment are presented.